Potentials of leaves of Aspilia africana (Compositae) in wound care: an experimental evaluation - Akah PA; Okoli CO; Okoli AS (BMC, 2007)
Abstract Background The potentials of the leaves of the haemorrhage plant, Aspilia africana C. D Adams (Compositae) in wound care was evaluated using experimental models. A. africana, which is widespread in Africa, is used in traditional medicine to stop bleeding from wounds, clean the surfaces of sores, in the treatment of rheumatic pains, bee and scorpion stings and for removal of opacities and foreign bodies from the eyes. The present study was undertaken to evaluate the potentials for use of leaves of this plant in wound care. Methods The effect of the methanol extract (ME) and the hexane (HF) and methanol (MF) fractions (obtained by cold maceration and graded solvent extraction respectively) on bleeding/clotting time of fresh experimentally-induced wounds in rats, coagulation time of whole rat blood, growth of microbial wound contaminants and rate of healing of experimentally-induced wounds in rats were studied as well as the acute toxicity and lethality (LD50) of the methanol extract and phytochemical analysis of the extract and fractions. Results The extract and fractions significantly (P < 0.05) reduced bleeding/clotting time in rats and decreased coagulation time of whole rat blood in order of magnitude of effect: MF>ME>HF. Also, the extract and fractions caused varying degrees of inhibition of the growth of clinical isolates of Pseudomonas fluorescens and Staphylococcus aureus, as well as typed strains of Ps. aeruginosa (ATCC 10145) and Staph. aureus (ATCC 12600), and reduced epithelialisation period of wounds experimentally-induced in rats. Acute toxicity and lethality (LD50) test in mice established an i.p LD50 of 894 mg/kg for the methanol extract (ME). Phytochemical analysis revealed the presence of alkaloids, saponins, tannins, flavonoids, resins, sterols, terpenoids and carbohydrates. Conclusion The leaves of A. africana possess constituents capable of arresting wound bleeding, inhibiting the growth of microbial wound contaminants and accelerating wound healing which suggest good potentials for use in wound care.